The Economic Approach to Political Borders - Enrico Spolaore (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper overviews theoretical and empirical contributions that study political borders from an economic perspective. It reviews theories of the number and size of nations focused on the trade-off between economies of scale in public-good provision and heterogeneity of preferences over public policies as well as on the factors affecting this trade-off, such as democratization, international openness, and conflict. It also reviews studies of political integration and disintegration that focus on economic inequality, redistribution policies, and the geographical distribution of resources. Finally, the paper discusses recent empirical studies that shed light on the relations among heterogeneity, conflict, and borders. This line of research is part of a growing literature on the interplay between cultural variables and economic and political outcomes.
Keywords: D70; D74; F50; F55; H10; H40; H77; N40; P00; 330; borders; economies of scale; public goods; federalism; decentralization; ethnicity; culture; conflict; Grenze; Staatsgebiet; Föderalismus; Grenzregion; Dezentralisierung; Skalenertrag; Öffentliche Güter; Kulturelle Identität; Neue politische Ökonomie